Protocol for in vitro BCR-mediated plasma cell differentiation and purification of chromatin-associated proteins - Kyoko Ochiai; Hiroki Shima; Tsuyoshi Ikura; Marissa C. Franke; Evelyn P. Sievert; Roger Sciammas; Kazuhiko Igarashi (STAR Protocols, 2021)
Summary: Molecular-level understanding of plasma cell (PC) differentiation has been modeled using lipopolysaccharide (LPS) stimulation in vitro. However, this system does not involve the B-cell receptor (BCR)—a critical component of B cell biology. Here, we present a protocol for in vitro PC differentiation system dependent on BCR signaling that easily scales up for cell number-demanding applications, including protein complex purification. We describe how to set up this system and detail applications for endogenous complex purification of chromatin-associated proteins.For further details on the use and execution of this protocol, please refer to Sciammas et al. (2011) and Ochiai et al. (2018, 2020).